Ultrasound parameters of the abdominal organs of tamandua (Tamandua tetradactyla) - Dupont T., Jenny (2018)
Tamandua (Tamandua tetradactyla) is a mammal that belongs to the superorder Xenarthra, family Myrmecophagidae, lonely animal with crepuscular habits. The objective of the study was to describe the topography, morphology, and location of the abdominal organs through an ultrasound evaluation. Five specimens of T. tetradactyla in captivity from the Huachipa Zoological Park, Lima, Peru (three adult males and two juveniles), in apparent good health conditions were used. A Pie Medical Ultrasound Falco Vet® Model 100 with a multifrequency convex transducer of 5-7.5 MHz was used. The topography, margins, shape, dimensions, echotexture and echogenicity of the abdominal organs were evaluated. The results did not differ from those found in dogs of the same size and weight. However, it has been found that the tamandua, like the Hoffmann's two-toed sloth lazy bear (Choloepus hoffmanni), has intra-abdominal testicles and the kidneys located between the flank and inguinal regions.